332 Beirut port blast: a multi-center study to assess injury characteristics and outcomes. (20th November 2022) - Al-Hajj, Samar; Farran, Sarah H; Zgheib, Hady; Tfaily, Mohamad Ali; Halaoui, Adham; Wehbe, Sarah; Karam, Stephanie; Fadlallah, Yaser; Fahd, Fares; Toufaili, Lana; Arjinian, Sebouh; Al-Zaghrini, Elie; et al.
Abstract : Importance: Understanding injuries and their outcomes in the Beirut Blast is vital to informing mass-casualty and disaster management strategies and improving injury outcomes for victims. Background: Blasts incidents impose catastrophic aftermaths on populations in terms of casualties, sustained injuries and devastated infrastructure. Lebanon witnessed one of the largest non-nuclear chemical explosions in modern history – the August 2020 Beirut Port Blast. This study assesses the mechanisms and characteristics of blast morbidity and mortality and examines the predictors of severe injury as measured by the Injury Severity Score (ISS). Design: A retrospective, multi-center cross-sectional study. Data were collected in a two-stage process involving patient hospital chart review and follow-up phone calls. Setting: Five major acute-care hospitals in metropolitan Beirut. Participants: Trauma patients presenting to participating hospitals up to 4 days following the blast. Main Outcomes: Injury severity and mortality following blast injury. Results: 791 patients were included with a median age of 42 years. The mean distance from the blast was 2.4 km (SD 1.9 km), 3.1% of victims were in the Beirut Port itself. The predominant mechanism of injury was being struck by an object (falling or projectile) (293, 37.0%) and the most frequent site of injury was the head or face (209, 26.4%). Injury severity was low for 548 (71.2%) patients, moderate for 62 (8.1%), and severe or critical for 27 (3.5%). Twenty-one deaths were recorded (2.7%). Significant predictors of serious injury (ISS>15) were sustaining multiple injuries (OR=2.62, p=0.005) including a fracture (OR= 5.78, p<0.001), primary injuries, specifically a blast lung (OR= 18.82, p=0.001), concussion (OR=7.17, p<0.001), and eye injury (OR=8.51, p<0.001). Secondary injuries overall, particularly penetrating injuries (OR=9.93, p<0.001) and traumatic amputations (OR=13.49, p=0.01). 25.0% were admitted to the hospital, with 4.6% requiring the ICU. At discharge, 25 patients (3.4%) had recorded neurologic disability. Conclusions and Relevance: Most injuries sustained by the blast victims were minor. Serious injuries were mostly linked to blast pressure and projectile fragments. Understanding the characteristics of blast injuries, their severity and their management are vital to informing emergency services, disaster management strategies and hospital preparedness and consequently improving patient outcomes.